Ecotoxicological assessment of cobalt using Hydra model: ROS, oxidative stress, DNA damage, cell cycle arrest, and apoptosis as mechanisms of toxicity. (May 2017) - Zeeshan, Mohammed; Murugadas, Anbazhagan; Ghaskadbi, Surendra; Ramaswamy, Babu Rajendran; Akbarsha, Mohammad Abdulkader
Abstract: The mechanisms underlying cobalt toxicity in aquatic species in general and cnidarians in particular remain poorly understood. Herein we investigated cobalt toxicity in a Hydra model from morphological, histological, developmental, and molecular biological perspectives. Hydra, exposed to cobalt (0–60 mg/L), were altered in morphology, histology, and regeneration. Exposure to standardized sublethal doses of cobalt impaired feeding by affecting nematocytes, which in turn affected reproduction. At the cellular level, excessive ROS generation, as the principal mechanism of action, primarily occurred in the lysosomes, which was accompanied by the upregulation of expression of the antioxidant genes SOD, GST, GPx, and G6PD. The number of Hsp70 and FoxO transcripts also increased. Interestingly, the upregulations were higher in the 24-h than in the 48-h time-point group, indicating that ROS overwhelmed the cellular defense mechanisms at the latter time-point. Comet assay revealed DNA damage. Cell cycle analysis indicated the induction of apoptosis accompanied or not by cell cycle arrest. Immunoblot analyses revealed that cobalt treatment triggered mitochondria-mediated apoptosis as inferred from the modulation of the key proteins Bax, Bcl-2, and caspase-3. From this data, we suggest the use of Hydra as a model organism for the risk assessment of heavy metal pollution in aquatic ecosystems. Graphical abstract: Highlights: Cobalt exposure affects morphology, histology, regeneration, and reproduction in Hydra . Cobalt-treated Hydra shows disordered feeding responses due to altered BCCs. Cobalt treatment induces ROS generation, apparently in the lysosomes. Cobalt exposure activates both adaptive and stress responses in Hydra . Cobalt induces DNA damage, cell cycle arrest, and apoptosis in Hydra . Abstract : As tested in Hydra, cobalt is a toxicant of aquatic ecosystems, manifesting its effects through the generation of ROS and bringing up changes leading to cell death through apoptosis.